A prospective study to determine etiology, clinical profile and neurodevelopmental outcome of neonatal seizures admitted in newborn unit of Chengalpattu Medical College and Hospital, Tamil Nadu, India - Kolkar, Yalaguraswami B.; Sailavasan, Madhivannan (International Journal of Contemporary Pediatrics, 2019)
Background: Newborn with neonatal seizures is at risk of neurodevelopmental delay. The aim of this study was to determine the factors affecting the adverse outcome of neonatal seizures and to study the significant factors associated with poor neurodevelopmental outcome in neonatal seizures. Methods: This was a prospective study done at neonatal intensive care unit (NICU) in Chengalpattu Medical College during the period from June 2017 to September 2018. A total of 110 neonates with seizures admitted in NICU from first hour of life to 28 days of age were included in the study. Detailed history was collected in preformed proforma, and followed up to one year and neurological assessment done at 4th month, 8th month and 1 year. The Hammersmith infant neurological examination (HINE) was done at 4 and 8 month and the Bayley–III assessment was done at 1 year of age to determine the neurodevelopment outcome. Results: Out of 110 newborns with seizures, 86 cases were followed up to 1 year of age. Neurological assessment done by HINE determined abnormal neurodevelopment in 33.6% neonates. Bayley-III scale assessment found cognitive delay in 10.9%, language delay in 20%, motor delay in 5.55%, socio-emotional delay in 30%, and adoptive delay in 31.8% cases. Delayed developmental outcome is significantly associated with onset of seizures, frequency of seizure, poor 5 minute Apgar score, abnormal EEG, and hypoxic ischemic encephalopathy (HIE). Conclusions: The delayed developmental outcome high among the neonates with subtle and myoclonic seizures. Mortality and neurological impairment was after neonatal seizure is associated with Onset and frequency of seizures, low Apgar score at 5 min, findings of USG cranium, CT brain, EEG, and HIE.